Effect of scanning strategy on grain structure and crystallographic texture of Inconel 718 processed by selective laser melting. Issue 10 (October 2018) - Wan, H.Y.; Zhou, Z.J.; Li, C.P.; Chen, G.F.; Zhang, G.P.
Abstract: Two types of scanning strategies were adopted to study the effect of scanning strategy on grain structure and crystallographic texture of selective laser melted (SLM) Inconel 718. The results show that bidirectional scanning without and with a 90°-rotation for every layer produced the bimodal grain structure and the directional columnar grain structure, respectively. Controlling the heat flux direction between the successive layers via scanning strategy enabled the formation of such different grain structures. Furthermore, when the 90°-rotation was applied, the competitive grain growth mechanism became more pronounced and the strong cube texture developed.